Antimicrobial and Herbal Drug Resistance in Enteric Bacteria Isolated from Faecal Droppings of Common House Lizard/Gecko (Hemidactylus frenatus) - Bhoj R. Singh; Vidya Singh; N. Ebibeni; Raj K. Singh (International Journal of Microbiology)
From 194 faecal dropping samples of common house geckos collected from offices (60), houses (88), integrated farm units (IFS,18) and hostels, guest houses, and dining rooms of different canteen/mess (HGM, 28), 326 bacterial isolates of enteric bacteria belonging to 17 genera and 34 species were detected. Escherichia coli were the most frequently (39) isolated followed by Citrobacter freundii (33), Klebsiella pneumonia (27), Salmonella indica (12), Enterobacter gergoviae (12), and Ent. agglomerans (11). Other important bacteria isolated from gecko droppings were Listonella damsela (2), Raoultella terrigena (3), S. salamae (2), S. houtenae (3), Edwardsiella tarda (4), Edwardsiella hoshinae (1), and Klebsiella oxytoca (2). Of the 223 isolates tested for antimicrobial drug sensitivity, 27 (12.1%) had multiple drug resistance (MDR). None of the salmonellae or edwardsiellae had MDR however, MDR strains were significantly more common among Escherichia spp. (P=1.9×10-5) and isolates from IFS units (P=3.58×10-23). The most effective herbal drug, Ageratum conyzoides extract, inhibited growth of only 27.8% of strains tested followed by ethanolic extract of Zanthoxylum rhetsa (13.9%), eucalyptus oil (5.4%), patchouli oil (5.4%), lemongrass oil (3.6%), and sandalwood oil (3.1%), and Artemisia vulgaris essential oil (3.1%).